2021
DOI: 10.1002/ccr3.4047
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of patient with neurofibromatosis type 1 in a genotype–phenotype correlation revealing a submicroscopic deletion on the long arm of chromosome 17

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(16 reference statements)
0
2
0
1
Order By: Relevance
“…This will certainly limit our ability to relate the clinical phenotype to the mutant genotype. To date, only 5 patients with non-mosaic type-2 NF1 deletions have been clinically characterized (Vogt et al 2011 ; Zhang et al 2015 ; Büki et al 2021 ; Yethindra et al 2021 ). From these data, it may be concluded that non-mosaic type-2 NF1 deletions are associated with a severe clinical phenotype similar to that exhibited by patients with type-1 NF1 deletions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This will certainly limit our ability to relate the clinical phenotype to the mutant genotype. To date, only 5 patients with non-mosaic type-2 NF1 deletions have been clinically characterized (Vogt et al 2011 ; Zhang et al 2015 ; Büki et al 2021 ; Yethindra et al 2021 ). From these data, it may be concluded that non-mosaic type-2 NF1 deletions are associated with a severe clinical phenotype similar to that exhibited by patients with type-1 NF1 deletions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been estimated that at least 70% of all type-2 NF1 deletions are of postzygotic origin (Steinmann et al 2007;Messiaen et al 2011). So far, only 5 patients with non-mosaic type-2 NF1 deletions have been reported (Vogt et al 2011;Zhang et al 2015;Büki et al 2021;Yethindra et al 2021). The reason why the paralogous sequences SUZ12 and SUZ12P are more often involved in mitotic NAHR and only rarely in meiotic NAHR giving rise to non-mosaic type-2 NF1 deletions, are unclear.…”
Section: Frequency Of Somatic Mosaicismmentioning
confidence: 99%
“…Az irodalomban csak néhány, klinikailag jól jellemzett eset ismeretes, amelynél a betegek a deletiót nem mozaikos formában hordozzák. A betegek tüneteit a 4. táblázatban foglaltuk össze [20,22,27,[33][34][35]. Az alacsony esetszám által indokolt mértéktartás mellett is kiemelhető az adatokból, hogy az 1-es típusú deletiós betegekhez hasonlóan a különböző típusú neurofibromák előfordulási gyakoriságában, a csontrendszert érintő manifesztációkban, a dysmorphiás jellemzőkben, illetve a magatartási és tanulási problémák tekintetében eltérések figyelhetők meg a pontmutációs betegcsoportokhoz képest.…”
Section: Az Nf1 Microdeletiók Vizsgálati Módszereiunclassified